The Song of Songs through the ages: essays on the Song’s reception history in different times, contexts, and genres - Schellenberg-Lagler, Annette (Studies of the Bible and its reception, 2023)
The Song of Songs is a fascinating text. Read as an allegory of God’s love for Israel, the Church, or individual believers, it became one of the most influential texts from the Bible. This volume includes twenty-three essays that cover the Song’s reception history from antiquity to the present. They illuminate the richness of this reception history, paying attention to diverse interpretations in commentaries, sermons, and other literature, as well as the Song’s impact on spirituality, theological and intellectual debates, and the arts